2014
DOI: 10.2147/cia.s74088
|View full text |Cite
|
Sign up to set email alerts
|

Primary percutaneous coronary intervention ameliorates complete atrioventricular block complicating acute inferior myocardial infarction

Abstract: ObjectiveComplete atrioventricular block (CAVB) in acute inferior ST-segment elevation myocardial infarction (STEMI) is associated with poor clinical outcomes after noninvasive treatment. This study was designed to determine the effect of primary percutaneous coronary intervention (PCI) in patients with CAVB complicating acute inferior STEMI, at a single center.MethodsWe enrolled 138 consecutive patients diagnosed with STEMI involving the inferior wall; of these, 27 patients had CAVB. All patients received pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The mechanism of HAVB in inferior wall STEMI is not fully elucidated. However, as mentioned in our previous study, 20 we consider that the underlying major cause of bradyarrhythmia results from the cardioinhibitory (Bezold–Jarisch) reflexes arising from vagal efferent nerves in the ischemic ventricular wall. In this study, we investigated the prognostic significance of TP in 72 patients with inferior STEMI treated with primary PCI.…”
Section: Discussionmentioning
confidence: 90%
“…The mechanism of HAVB in inferior wall STEMI is not fully elucidated. However, as mentioned in our previous study, 20 we consider that the underlying major cause of bradyarrhythmia results from the cardioinhibitory (Bezold–Jarisch) reflexes arising from vagal efferent nerves in the ischemic ventricular wall. In this study, we investigated the prognostic significance of TP in 72 patients with inferior STEMI treated with primary PCI.…”
Section: Discussionmentioning
confidence: 90%
“…cardiogenic shock, intra-ventricular arrhythmias, and increased risk of in hospital mortality [1416]. Experience with complete AV block in patients with STEMI have shown that CHB respond to atropine and isoproterenol in the vast majority of cases and usually it does not require even temporary pacing and almost never implantation of permanent pacemakers [17, 18]. However current guidelines have recommended that temporary pacing is indicated for symptomatic bradyarrythmias unresponsive to medical treatment [19].…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve clinical outcomes in patients with AMI, it is essential to collect more specific data about each complication of AMI. High-degree atrioventricular block (HAVB) is a common complication following ST-segment elevation myocardial infarction (STEMI), the incidence of which is reported to be 2.7 to 19.6% [3][4][5][6][7]. Each complication of AMI depends on the size and anatomic location of the infarction, and HAVB is more common in inferior STEMI [3,4].…”
Section: Introductionmentioning
confidence: 99%